Perceived Procedural Organizational Justice Matters for the Success of Quality Policies - Pérez-Arechaederra, Diana; García Ortiz, Luis; Mora, Sara (Pontificia Universidad Católica del Perú. CENTRUM, 2015)
The purpose of the study was to investigate the role of perceptions of organizational justice in the relationship between changes to improve service quality and the level of job satisfaction of health care workers. The method was to use the fairness heuristic theory framework to compare workers from a primary health care center applying European Foundation for Quality Management (EFQM) practices with workers from centers not applying any quality policy (n = 95). Results show that the EFQM workers reported higher ratings of procedural justice than workers without EFQM, although their satisfaction levels were not significantly different. Furthermore, the application of the EFQM model showed a moderating influence on the relationship between procedural justice and satisfaction. Thus, in a changing environment, procedural justice had a strong effect on workers’ satisfaction. The value of the study is to deepen the understanding of how quality practices and organizational changes influence workers’ perceptions and attitudes towards their work environment.
Keywords: EFQM; Organizational justice; Fairness heuristic theory (FHT); Health care workers; Job satisfaction; Quality management; https://purl.org/pe-repo/ocde/ford#5.02.04